Gender Roles in Dahlia Rasyad’s Novel Perempuan Yang Memetik Mawar: Talcott Parsons’ Perspective - Andi Indah; Anshari Anshari; Usman Usman; N. Ifga Gunawan (JENTERA: Jurnal Kajian Sastra, 2026)
The purpose of this study is to analyze the constructed gender roles in Dahlia Rasyad’s novel Perempuan yang Memetik Mawar using a gender sociology perspective, specifically structural-functional theory (Parsons, 1949; Parsons & Bales, 1995). This study employs a qualitative research design with a descriptive method. The data in this study consist of words, phrases, and sentences from the primary data source, namely Dahlia Rasyad’s novel Perempuan yang Memetik Mawar, collected through the read-and-record technique. The data were analyzed through data reduction, data presentation, and drawing conclusions, which were then verified using source and theoretical triangulation. The results of the study indicate that this novel constructs traditional gender roles, in which women perform expressive roles (domestic, nurturing, providing emotional support) and men perform instrumental roles (public, earning a living). However, the study also identified representations of masculine women who work hard and earn a living, as well as feminine men who perform domestic work and provide emotional support. This study contributes to the field of gender sociology while serving as a vehicle for social critique of gender inequality in Indonesian society, particularly within the context of the local culture of South Sumatra. Abstrak Tujuan penelitian ini yaitu menganalisis peran gender yang dikonstruksikan dalam novel Perempuan yang Memetik Mawar karya Dahlia Rasyad menggunakan perspektif sosiologi gender, yaitu teori struktural fungsional oleh Parsons (1949) dan Parsons & Bales (1995). Jenis penelitian yang digunakan adalah penelitian kualitatif dengan metode deskriptif. Data dalam penelitian ini adalah kata, frasa, dan kalimat dari sumber data utama, yaitu novel Perempuan yang Memetik Mawar, yang dikumpulkan melalui teknik baca dan catat. Analisis dengan cara reduksi data, penyajian data, serta penarikan kesimpulan kemudian diverifikasi menggunakan triangulasi sumber dan teori. Hasil penelitian menunjukkan bahwa novel ini mengonstruksikan peran gender tradisional di mana perempuan menjalankan peran ekspresif (domestik, mengasuh, memberi dukungan emosional) dan laki-laki menjalankan peran instrumental (publik, mencari nafkah). Namun, ditemukan pula representasi perempuan maskulin yang bekerja keras dan mencari nafkah, serta laki-laki feminim yang melakukan pekerjaan domestik dan memberi dukungan emosional. Penelitian ini memberikan kontribusi dalam studi sosiologi gender, sekaligus menjadi sarana kritik sosial terhadap ketidaksetaraan gender dalam masyarakat Indonesia, khususnya dalam konteks budaya lokal Sumatera Selatan.